Activation of IGF-1 receptors and Akt signaling by systemic hyperinsulinemia contributes to cardiac hypertrophy but does not regulate cardiac autophagy in obese diabetic mice. (December 2017) - Pires, Karla Maria; Buffolo, Marcio; Schaaf, Christin; David Symons, J.; Cox, James; Abel, E. Dale; Selzman, Craig H.; Boudina, Sihem
Abstract: Autophagy plays an important role in the maintenance of normal heart function. However, the role of autophagy in the inulin resistant and diabetic heart is not well understood. Furthermore, the upstream signaling and the downstream targets involved in cardiac autophagy regulation during obesity and type 2 diabetes mellitus (T2DM) are not fully elucidated. The aim of this study was to measure autophagic flux and to dissect the upstream and downstream signaling involved in cardiac autophagy regulation in the hearts of obese T2DM mice. Our study demonstrated that cardiac autophagic flux is suppressed in the heart of obese diabetic ( ob/ob ) mice due to impaired autophagosome formation. We showed that suppression of autophagy was due to sustained activation of mTOR as we could restore cardiac autophagy by inhibiting mTOR. Moreover, the novel finding of this study is that while IGF-1 receptor-mediated Akt activation contributes to cardiac hypertrophy, it is not involved in mTOR activation and autophagy suppression in obesity and T2DM. In contrast, inhibition of ERK signaling abolished mTOR activation and restored autophagy in the heart of obese diabetic ( ob/ob ) mice. The study identifies mechanisms regulating cardiac autophagy in obesity and T2DM that are mediated by ERK/mTOR but are distinct from Akt. The findings are of significant importance as they demonstrate for the first time the contribution of IGF-1 receptors (IGF-1R) and Akt signaling in cardiac hypertrophy but not in cardiac autophagy regulation in obesity and T2DM. Graphical abstract: Highlights: Hyperinsulinemia activates cardiac IGF-1 receptors in obese type 2 diabetic mice. Cardiac autophagy is suppressed in obese type 2 diabetic mice through mTOR/ERK signaling. Cardiac hypertrophy in obese type 2 diabetic mice is mediated by IGF-1 receptors/Akt.